Implementation of The Merdeka Curriculum to Address Learning Loss in X-Grade Students at SMA Al-Islam 1 Surakarta - Awadian, Amelia Qanitah; Wisesa, Anggara (Universitas Muhammadiyah Surakarta, 2023)
The success of businesses like Fujifilm and Kodak has highlighted the need for exceptional leadership skills to navigate the challenges of a VUCA environment. This volatile, uncertain, complex, and ambiguous landscape requires leaders to adapt their strategies constantly. Effective leadership is crucial not only for large corporations but also for startups in the mental health industry. In Bandung, Indonesia, a mental health service is facing difficulties in expanding its customer base, mainly due to the novelty and popularity of mental health topics in the country. The CEO of the startup lacks assertiveness and heavily relies on the decisions of other team members to achieve goals. To address this issue, a study was conducted using an ethnographic approach to identify the most suitable leadership style. By examining human behavior from a holistic and culturally rich perspective, the researchers interviewed the co-founders of the mental health startup and analyzed the data using James Spradley's Ethnography Analysis. The findings reveal that the current leadership approach within the mental health startup is ineffective. Despite the co-founders' preference for various leadership styles to improve their performance, they express a desire for a transactional leadership style to be implemented.